STRATEGI KOMUNIKASI DAKWAH DIGITAL DALAM PENGUATAN MODERASI BERAGAMA - Ash Shiddieqy, Muhammad Dicky Hasbi (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2024)
The proliferation of religious content containing intolerance and extremism on social media has become a serious threat to the social cohesion of Indonesia’s pluralistic society. In this context, various moderate Islamic institutions have sought to utilize digital platforms as arenas for promoting values of religious moderation. One of the most prominent is NU Online through its official Instagram account, which consistently produces and distributes visual da’wah content based on moderation.This study aims to analyze the digital da’wah communication strategies implemented by the NU Online Instagram account in strengthening the values of religious moderation, with a focus on the dimension of the visual content it produces. The approach used is qualitative, employing methods of social semiotic analysis and framing analysis of visual content published on the NU Online Instagram account. Data were collected through systematic observation, content documentation, and literature review of relevant theoretical sources. The findings reveal that NU Online applies three main strategies in its visual content: (1) the strategy of symbolizing wasathiyyah (moderation) values through inclusive graphic design elements, (2) a visual narrative strategy of counter-radicalism that proactively responds to current issues, and (3) a framing strategy of moderate Muslim identity that emphasizes local Nusantara aesthetics. These three strategies collectively form an effective digital da’wah ecosystem in building and strengthening the discourse of religious moderation in Indonesia’s digital public sphere